GFF Guidance Note: Inclusive Multi-stakeholder Country Platforms in Support of Every Woman Every Child - Global Financing Facility (Global Financing Facility, 2018)
The aims of this paper are: 1) to highlight how multi-stakeholder country platforms, built on development effectiveness principles, in line with the globally agreed recommendations of IHP+2, can be reinforced within the framework of the Global Strategy and its supporting mechanisms and are key to the Global Strategy’s successful implementation; and 2) to lay out key considerations for new multi-stakeholder country platforms, along with the relevant mechanisms and a minimum set of standards to support the process of national coordination among actors engaged in RMNCAH. This guidance note is intended to serve as a resource for countries committed to implementing the Global Strategy. This includes the 62 high-burden, low- and lower-middle income countries that are eligible to receive resources from the GFF Trust Fund. It will build on lessons from countries that have already developed or are currently developing prioritized RMNCAH Strategies or Investment Cases (IC)4 aligned with their broader national health plans and planning cycles and processes, for purposes of mobilizing resources, including from the GFF Trust Fund and other sources of funding. The GFF, H6 and PMNCH seek to bring together a broad set of partners and leverage their unique roles, comparative advantages and value added to maximize impact for improved outcomes for women, children and adolescents.
Keywords: #Policy Document / Documento de Política; *indexed; *tagged; G - Rest of the World / Resto do Mundo; GFF (Global Financing Facility); Health PEA; L - english / inglês; civil society / sociedade civil; development partners / parceiros de cooperação; gender / género; health / saúde; youth / juventude

Youth initiatives: Supporting citizen engagement with government and civic life - Orrnert, Anna (GSDRC, University of Birmingham, 2018)
There is a large volume of literature on youth participation in development, including on the benefits of involving young people in local, national, regional and global governance initiatives. Although not as voluminous, there is also a significant body of work on youth participation in civic life, though much of this focuses on issues of education and employment (Oxfam 2016) as well as health (particularly initiatives related to HIV/ AIDS). It was not possible to identify a large body of literature around more multi-faceted and holistic initiatives (for example, involving different themes and connecting at different levels).
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; citizenship & participation / cidadania e participação; civil society / sociedade civil; youth / juventude

GFF Civil Society Engagement Strategy Addendum - Adolescent and Youth (AY) - Global Financing Facility (Global Financing Facility, 2018)
The Global Strategy for Women’s, Children’s and Adolescents’ Health 2016-30 highlights the importance of adolescent health and well-being as being essential to achieving the Sustainable Development Goals (SDG) by 2030. For adolescents to survive, thrive and transform their societies, the global community needs to invest in their health and well-being. Today’s adolescents are well-positioned to mobilize their peers, advocate for increased resources for sexual and reproductive health and rights, influence their governments to invest in addressing their needs, and demand accountability for commitments related to their health and development. The Global Financing Facility (GFF) Civil Society Engagement Strategy (CSES) and related implementation plan provide a clear framework for civil society organizations’ (CSOs) contribution to the improvement of health outcomes through coalition strengthening, meaningful participation in multi-stakeholder country platforms responsible for coordinating health plans and their implementation,1 and coordinated action in support of the achievement of national sexual, reproductive, maternal, newborn, child and adolescent health (SRMNCAH) goals. Youth and adolescent led organizations should use the CSES as the basis for their engagement in the GFF processes both at the global and national levels. This Adolescent and Youth (AY) addendum to the CSES outlines a deliberate approach to ensuring youth representation in the processes led by the GFF Civil Society Coordinating Group2 (CSCG) to ensure their meaningful and active participation in the design, implementation, monitoring and evaluation of their country investment case.
Keywords: #Policy Document / Documento de Política; *indexed; *tagged; G - Rest of the World / Resto do Mundo; GFF (Global Financing Facility); Health PEA; L - english / inglês; development partners / parceiros de cooperação; health / saúde; youth / juventude

Challenges and Strategies in Place-Based Multi-Stakeholder Collaboration for Sustainability: Learning from Experiences in the Global South - Ayala-Orozco, Bárbara; Rosell, Julieta A.; Merçon, Juliana; Bueno, Isabel; Alatorre-Frenk, Gerardo; Langle-Flores, Alfonso; Lobato, Anaid (Sustainability, 2018)
Addressing complex environmental problems requires the collaboration of stakeholders with divergent perspectives, a goal that is challenged by diverse factors. Challenges hindering multi-stakeholder collaboration (MSC) for sustainability have previously been addressed in the context of transnational partnerships. However, less is known regarding how place-based MSC operates, especially in the context of the Global South. To contribute to addressing the factors that hinder place-based MSC for sustainability in the Global South, we analyzed 38 MSC projects spanning diverse ecological and social contexts across Mexico. In a series of participatory workshops, 128 stakeholders from academia, government, business, local communities, and civil society organizations discussed factors that hinder place-based MSC and co-constructed strategies to strengthen collaboration. Some challenges coincided with those identified in previous studies (e.g., divergent visions, inadequate project planning), whereas other concerns that have not been commonly regarded as important emerged as crucial obstacles for MSC. We discuss these challenges in the context of areas of limited statehood and point to the traditions of popular education and participatory action research as a source of valuable tools for place-based MSC. We identify strategies capable of addressing diverse challenges, a result that could aid prioritizing resource allocation to strengthen MSC.
Keywords: G - Rest of the World / Resto do Mundo; L - english / inglês; collaboration / colaboração

Elevating Indonesia's Performance in Ease of Doing Business Index (Policy Reforms to Improve the 'Starting a Business' Indicator) - Freddy, Imelda Magdalena; Saputri, N. (2018)
Indonesian President Joko Widodo has set a target of improving the country’s ranking in The World Bank’s Ease of Doing Business (EODB) index from 72nd to 40th by 2019. One barrier to meeting this challenge is Indonesia’s ranking in the Starting a Business Indicator, where it is 144th among 190 countries. According to the EODB Report, it takes 23 days and 11 procedures to register a business in Indonesia. To address this problem, the central government has implemented changes requiring parallel procedures with local governments and introduced a program called the Online Single Submission system (OSS), established in July 2018. However, there are major barriers to the success of these changes, including a lack of information for businesses, inadequate IT infrastructure, and failure to synchronize the central and local governments under the OSS. As a result, policy changes and the OSS have not been working as intended. Case studies in Jakarta, Bandung, and Bandar Lampung revealed that there are two regulations—one implemented by the local government and the other implemented by the central government—that should be revised to speed up business registration. The government should also remove a procedure from the business registration process and develop collaboration with local private sectors and business associations to improve the OSS. These changes would reduce the time required for registering a business by 17 days. These reforms would benefit small and medium businesses the most, since they are the most common types of business in Indonesia (approximately 98% of all businesses). Such a reduction in the time required to register a business would be enough to improve Indonesia’s Starting a Business Indicator ranking from 144th to 75th. Based on our findings, we recommend four policy changes. First, the Jakarta provincial government should revise the Regulation of the Head of Investment and One Stop Integrated Services 23/2017 Article 2d. The Mandatory Labor Affairs Report (MLAR) stipulated in this regulation should be removed as a business registration requirement. Its content is duplicates data provided by the BPJS Ketenagakerjaan documents as part of national social security program. In addition, requiring an MLAR contradicts the regulation of the Minister of Manpower (MOM) 14/2006, which says it is not required for business registration. Second, Government Regulation 24/2018 Article 78 should be reformed to require that the central government collaborate with local business associations to disseminate information about the OSS. This collaboration will ensure that information reaches even remote areas. Third, Government Regulation 24/2018 Article 88 should be reformed to ensure that the ministries related to the OSS assist local governments to synchronize standard operating procedures and regulations to implement the OSS. This assistance should continue for one year, after which there should be a penalty for local governments that fail to comply with the new procedures for registering businesses through the OSS. Fourth, Government Regulation 24/2018 Article 91 should be changed to ensure the government will collaborate with the private sector to improve the IT infrastructure in all regions to support the OSS. Participation by the private sector is important because they have the resources to provide internet access and computers needed to implement the OSS in districts and municipalities across Indonesia.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA

How do gender relations affect the working lives of close to community health service providers? Empirical research, a review and conceptual framework - Steege, Rosalind; Taegtmeyer, Miriam; McCollum, Rosalind; Hawkins, Kate; Ormel, Hermen; Kok, Maryse; Rashid, Sabina; Otiso, Lilian; Sidat, Mohsin; Chikaphupha, Kingsley; Datiko, Daniel Gemechu; Ahmed, Rukhsana; et al. (Social Science & Medicine, 2018)
Close-to-community (CTC) providers have been identiﬁed as a key cadre to progress universal health coverage and address inequities in health service provision due to their embedded position within communities. CTC providers both work within, and are subject to, the gender norms at community level but may also have the potential to alter them. This paper synthesises current evidence on gender and CTC providers and the services they deliver.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; government policy / politica governamental; health - maternal and child / saúde - materno-infantil; health / saúde

The Importance of Lender-borrower Relationships to the Availability of Small and Micro Credit: Case Study on Indonesian Kredit Usaha Rakyat Loans - Suryani, Embun (International Journal of Economics and Financial Issues; Mersin, 2018)
This study aims to examine how the relationships between a borrower and his potential lender affect the decisions of potential lender whether or not to provide or extend funds to the borrower. The author explores the available literature and original fieldwork to create a framework to capture this relationship. The study employs descriptive qualitative data to analyze and examine the research questions. The result shows that borrowers who build their commercial transactions with their lender on intensive relationships are more likely to receive and extend loans. The relationship effects arise because it motivates both lender and borrower to share private resources and facilitate access to loan opportunities, but does not influence the price of loans. To sum up, the lender-borrower relationships are valuable and seem to operate through quantities, trust and the length of these relationships. Furthermore, these relationships are more appropriate to be implemented for small and micro-lending.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; ⛔ No DOI found

The Performance of Indonesia’s Public Credit Guarantee Scheme for MSMEs: A Regional Comparative Perspective - Tambunan, Tulus T.H. (Journal of Southeast Asian Economies, 2018)
Access to finance has been a key constraint for Indonesia’s micro, small and medium enterprises (MSMEs) that lack tangible assets to be used as collateral. Consequently, credit guarantee schemes (CGSs) are important instruments to meet MSMEs’ financial needs. This paper examines the effectiveness of the KUR (community business credit), a partial public CGS in Indonesia, by comparing it with similar schemes in other ASEAN member states (AMS). The findings suggest that the KUR programme, despite its limited coverage, has been quite effective throughout the country. Some of the critical factors behind its success include: wide dissemination of the programme; simplicity of the application procedure; full participation and support from banks; and strong coordination between all stakeholders.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA

Regional disparities in fertility preferences and demand for family planning satisfied by modern methods across levels of poverty: Mozambique An Analysis Brief from The DHS Program - USAID (USAID, 2018)
The DHS Analytical Studies 71 examines subnational variations in fertility preferences and family planning outcomes associated with poverty in married women in 12 recent Demographic and Health Surveys. Poverty is measured based on a standard set of criteria for unsatisfied basic needs and the ownership of specific assets. Households are categorized into three poverty groups: not extremely poor, extremely poor but not asset poor, and extremely poor and asset poor. This brief summarizes the results from the Democratic Republic of The Congo based on the 2013-14 DHS on regional variations in poverty, regional estimates of mean ideal number of children, and demand for family planning satisfied by modern methods, for each poverty group among married women.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; Health PEA; L - english / inglês; Northern PEA; demographics / demografia; gender / género; health / saúde; poverty / pobreza